Association of BRAF V600E mutations with vasoactive intestinal peptide syndrome in MYCN‐amplified neuroblastoma. Issue 10 (31st July 2021) - Shahid, Sanam; Kushner, Brian H.; Modak, Shakeel; Basu, Ellen M.; Rubin, Elyssa M.; Gundem, Gunes; Papaemmanuil, Elli; Roberts, Stephen S.
Abstract: Very rarely, vasoactive intestinal peptide‐related diarrhea (VIP‐D) is observed in patients with high‐risk neuroblastoma (HR‐NB) where the associated fluid and electrolyte abnormalities can pose a major clinical challenge for administering the required aggressive multimodality treatment. Two patients with HR‐NB developed VIP‐D during induction and were found to have a somatic BRAF V600E mutation. Serum VIP levels and diarrhea promptly resolved in both patients after initiating treatment with BRAF and MEK inhibitors. This illustrates an association of VIP‐D with BRAF V600E mutations and demonstrates a therapeutic strategy in the specific context of VIP‐D and BRAF V600E mutations in HR‐NB patients. The addition of BRAF and MEK inhibitors allows continued conventional tumor‐directed treatment by decreasing the severity of symptoms caused by this life‐threatening complication.